Caracterização físico-química, energética e sensorial de hidromel - Brunelli, Luciana Trevisan [UNESP] (2015)
Mead is a good income option for honey producers (value added), allowing the development of a commercially little known drink in several countries, but it has great commercial potential. The objective of this work was to produce and analyze physicochemical and sensory fermented honey produced from the combination of three types of honey (eucalyptus, orange and sylvan) and different soluble solids concentrations in the initial must (20, 30 and 40 ºBrix). The experimental design was completely randomized with nine treatments and three repetitions, totaling 27 experimental units. After dilution of the honey, inoculation was carried out with dry yeast. Fermentation took place at room temperature (18-25º C) and monitored daily until the stabilization of the soluble solids content (ºBrix). After the end of the fermentation drawing off a was made. The fermentation was held at room temperature (18-22ºC). After this period, the first racking was made and fermented beverage remained at rest for 30 days. In the second separation, beverages were bottled in green glass bottles of 750 ml capacity. The meads were analyzed for pH, total, volatile and fixed acidity, alcohol content, total reducing sugars (TRS), dry extract, reduced dry extract, color and turbidity. Sensory analysis was made by acceptance testing - hedonic scale. The statistical analysis (ANOVA) for physicochemical and sensory analysis was done by F test and the treatment means compared by Tukey test at 5% probability. The increase in the proportion of honey in the formulation interferes in physicochemical and sensory parameters of meads. Beverages prepared with higher concentrations of raw material (honey) have higher acceptability.